Nanoplatforms in sepsis storm: Multimodal synergy for precision immunomodulation and pathogen neutralizations - Xinxin Wang; Xuemei Wang; Yuxin Cao; Wenming Wang; Dandan Liu; Jingwen Zhang; Yuxiu Chen; Daquan Chen (Pharmaceutical Science Advances)
Sepsis, a severe global health challenge characterized by life-threatening organ dysfunction stemming from a dysregulated immune response to drug-resistant pathogens, imposes a substantial disease burden. The intricate nature of sepsis necessitates meticulous drug administration and underscores the urgency for advanced drug delivery strategies. This paper presents a comprehensive overview of recent advancements in nanotechnology-driven therapeutic interventions for sepsis, emphasizing innovative approaches such as stimulus-responsive and nano-drug delivery systems that have been applied to tackle sepsis and its associated complications. Drawing from various theories and mechanistic insights into sepsis pathogenesis, we explore novel therapeutic avenues and their potential integration with nano-delivery systems, considering factors such as the microenvironment. We demonstrate how these nano-delivery systems can enhance treatment accuracy and diversity. Furthermore, the synergy between nanomedicine and emerging technologies like CRISPR, CAR-T therapy, AI, microfluidics, microbiome research, and immunotherapy holds the promise to revolutionize sepsis diagnosis, treatment, and management strategies. However, overcoming pathogen resistance, precisely modulating excessive immune response/immunosuppression, and achieving efficient targeted delivery of nanocarriers in complex pathological environments remain core challenges. Future research needs to focus on the development of smarter and more responsive nanoplatforms and deeply explore their deep integration with multiple cutting-edge technologies in order to advance the clinical translation of precision sepsis diagnosis and treatment.